Legal Protection of Workers in Employment Termination Disputes in North Sumatra: Between Legal Certainty and Social Justice - Rika Jamin Marbun; Rahmayanti (CV. RADJA PUBLIKA, 2025)
This study analyzes the legal protection of workers in employment termination disputes in North Sumatra by examining the relationship between legal certainty and social justice. Employment termination remains a critical labour issue because it affects workers’ economic security, access to welfare, and bargaining position in industrial relations. Although Indonesian labour law provides formal protection through termination procedures, severance rights, compensation mechanisms, and industrial relations dispute settlement, practical barriers continue to limit workers’ access to substantive justice. This study applies a socio-legal approach by examining statutory regulations, relevant legal documents, court-related materials, and the practical context of employment termination disputes in North Sumatra. The findings show that legal protection is formally available through Law No. 13 of 2003, Law No. 2 of 2004, Law No. 6 of 2023, and Government Regulation No. 35 of 2021. However, workers still face unequal bargaining power, limited legal knowledge, financial constraints, lengthy dispute resolution processes, and difficulties in enforcing their rights. Employment termination disputes in North Sumatra commonly involve the legality of termination, procedural compliance, severance pay, compensation rights, and access to dispute resolution mechanisms. The study concludes that effective worker protection cannot rely solely on formal legal certainty, but must also incorporate social justice through accessible, fair, and responsive dispute resolution. This article contributes to labour law scholarship by offering a regional socio-legal analysis that integrates legal certainty and social justice in employment termination disputes.